2000
DOI: 10.1021/jp0021188
|View full text |Cite
|
Sign up to set email alerts
|

Photoionization Spectroscopy of the Zinc Monoethyl Radical and Its Cation

Abstract: The spectra of the ZnC 2 H 5 radical and its cation have been recorded by two photoionization techniques, resonantly enhanced multiphoton ionization and zero electron kinetic energy spectroscopy, respectively. The ionization potential of the radical has been determined along with a number of vibrational frequencies in the ground state of the cation and the excited state of the neutral. Based upon the spectroscopic data, models for the metal-carbon bonding in metal alkyl radicals are proposed that predict relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…where ω is the interval of averaging around ω = ν/c. The Franck-Condon factors are tabulated for many molecular transitions in [25], or they can be calculated by a computer code [26].…”
Section: Molecular Absorption-diatomic Moleculesmentioning
confidence: 99%
“…where ω is the interval of averaging around ω = ν/c. The Franck-Condon factors are tabulated for many molecular transitions in [25], or they can be calculated by a computer code [26].…”
Section: Molecular Absorption-diatomic Moleculesmentioning
confidence: 99%
“…64 Of note is the application of the technique to organometallic species for the first time. The latter is a field opened by Miller and coworkers at The Ohio State University, and detailed studies of ZnCH 3 , 65 CdCH 3 , 66 MgCH 3 65 and ZnC 2 H 5 67 have been reported. In the present work, we concentrate on CdCH 3 , the first organometallic molecule to have been studied, and MgCH 3 , since its cation is the epitome of a Grignard reagent.…”
Section: Metal-containing Speciesmentioning
confidence: 99%